ANALISIS SERVICE EXPERIENCE PADA PENGGUNA TRANSPORTASI BUS WISATA MPOK SITI (BUS JAKARTA EXPLORER) - Firra Kholisha Mustika; Fahrurozy Darmawan; Devi Roza K.Kausar (Journal of Tourism Destination and Attraction, 2019)
The Mpok Siti Tourists Bus (Jakarta Explore Bus) is established by Jakarta Provincial Government to support the tourism sector by enhancing accessibility. This tour bus offers a tour service around the city of Jakarta. The purpose of this study is to explore service experience of the tour bus users and identify gaps in service experience using importance performance analysis. Survey was developed based on the following service experience dimensions: incentives, accessibility, comfort, utility, environment, benefits and trust. The research design used quantitative descriptive method through purposive sampling with the number of respondents as many as 100 people. Data processing techniques use the importance of performance analysis carried out by the excel program and SPSS 22.0. The results of analysis obtained the level of suitability between importance and performance at 96 percent on incentives, trust at 98 percent and accessibility at 84 percent. From survey conducted, it is also revealed that users have not considered the value of education as important in using the service, higher importance score was seen on the ease of traveling and physical appearance of the bus.